Occurrence data of southern butterflies in South Korea - Hyun Woo Kim; Youngho Cho; Pradeep Adhikari; Ja-Young Jeon; Yong-gu Han; Changwan Seo (Geo Data, 2020)
Background In Northern hemisphere, climate change has shifted the habitats of many species including butterflies into the northern regions. Many researchers in Europe and North America have reported this type of northward shift of butterflies. Thus, we collected the species occurrence data of southern butterflies and presented in this study for understanding the impact of climate change on the southern butterflies in the future. New information This study presents the 456 occurrence data of nine southern butterflies under five families in Korea. These data were selected from the 3rd National Ecosystem Survey (NES) conducted by National Institute of Environment Research (NIER) in Korea. Those will be a part of input data for MOTIVE-Ecosystem model, an integrative model to understand the influence of climate change and land cover change on the habitat suitability of sensitive, native and invasive species. These data will be important to the researchers and conservation agencies for understanding the current conditions of southern butterflies and developing conservation policy.